Using patterned supported lipid membranes to investigate the role of receptor organization in intercellular signaling - Nair, Pradeep M (2011)
physical inputs, both internal and external to a cell, can directly alter the spatial organization of cell surface receptors and their associated functions. Here we describe a protocol that combines solid-state nanolithography and supported lipid membrane techniques to trigger and manipulate specific receptors on the surface of living cells and to develop an understanding of the interplay between spatial organization and receptor function. While existing protein-patterning techniques are capable of presenting cells with well-defined clusters of protein, this protocol uniquely allows for the control of the spatial organization of laterally fluid receptor-ligand complex at an intermembrane junction. a combination of immunofluorescence and single-cell microscopy methods and complementary biochemical analyses are used to characterize receptor signaling pathways and cell functions. the protocol requires 2–5 d to complete depending on the parameters to be studied. In principle, this protocol is widely applicable to eukaryotic cells and herein is specifically developed to study the role of physical organization and translocation of the EphA2 receptor tyrosine kinase across a library of model breast cancer cell lines.